2012
DOI: 10.1021/la300975s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dipole–Dipole Interactions on Coverage-Dependent Adsorption: CO and NO on Pt(111)

Abstract: Density functional theory (DFT) calculations of energetic, geometric, vibrational, and electrostatic properties of different arrangements of CO and NO at quarter and half monolayer coverage on Pt(111) are presented. Differences in the extents of electron back-donation from the Pt surface to these molecules cause the low-coverage adsorbate dipoles to have opposite signs at atop and more highly coordinated bridge or fcc sites. These dipoles of opposite sign occupy adjacent positions in the experimentally observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
90
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 47 publications
14
90
0
Order By: Relevance
“…49 They are mediated by adsorbate-induced modification of the local electron density 50,51 or by dipole-dipole interactions. 52 Recent theoretical work, using improved potential energy surfaces, revealed that the angular degrees of freedom of CO on copper play an important role in energy redistribution between vibrational states. 53 Nearby adsorbates could easily influence these angular states.…”
Section: Discussionmentioning
confidence: 99%
“…49 They are mediated by adsorbate-induced modification of the local electron density 50,51 or by dipole-dipole interactions. 52 Recent theoretical work, using improved potential energy surfaces, revealed that the angular degrees of freedom of CO on copper play an important role in energy redistribution between vibrational states. 53 Nearby adsorbates could easily influence these angular states.…”
Section: Discussionmentioning
confidence: 99%
“…9 Adsorbates in close proximity tend to interact, leading to coverage-dependent binding energies, 8,[10][11][12] and activation energies sensitive to co-adsorbates. 13 Through-surface electronic effects, 14 surface strain, 12 and through-space electrostatics 15 are but a few of the many mechanisms by which adsorbates can interact.…”
mentioning
confidence: 99%
“…This behavior could be explained by different local dipole moments of CO at the two different adsorption sites 19 . Later calculations showed that the dipole moment of CO has indeed opposite sign when adsorbed on the bridge site as compared to the atop site 23 . It is known that the small dipole moment of CO depends on the strength of the bonding to a metal surface, 24 and a change of adsorption site could lead to the observed change of polarity.…”
Section: The Systemmentioning
confidence: 99%